PENGARUH EARNINGS MANAGEMENT DENGAN POLITICAL CONNECTION SEBAGAI VARIABEL MODERASI TERHADAP TAX AVOIDANCE - Utomo, Fidella Azalia; Akhadi, Iman (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This study aims to obtain empirical evidence regarding the influence of earning management, moderated by political connection, firm size, leverage, profitability, independent board of commissioners, and sales growth on tax avoidance. The population used in this research consists of companies in the non-cyclical consumer and cyclical consumer sectors listed on the Indonesia Stock Exchange (IDX) during the period from 2020 to 2022. The sample, obtained using purposive sampling methods, comprises 60 companies with a total of 180 data points. Data analysis was conducted using multiple linear regression methods, revealing that firm size, profitability, and sales growth significantly affect tax avoidance. In contrast, earning management moderated by political connections, leverage, and independent board of commissioners does not have a significant impact on tax avoidance.